TALE-directed local modulation of H3K9 methylation shapes exon recognition - Bieberstein, Nicole I; Kozáková, Eva; Huranová, Martina; Thakur, Prasoon K; Krchňáková, Zuzana; Krausová, Michaela; Carrillo Oesterreich, Fernando; Staněk, David (Scientific reports, 2016)
In search for the function of local chromatin environment on pre-mRNA processing we established a new tool, which allows for the modification of chromatin using a targeted approach. Using Transcription Activator-Like Effector domains fused to histone modifying enzymes (TALE-HME), we show locally restricted alteration of histone methylation modulates the splicing of target exons. We provide evidence that a local increase in H3K9 di- and trimethylation promotes inclusion of the target alternative exon, while demethylation by JMJD2D leads to exon skipping. We further demonstrate that H3K9me3 is localized on internal exons genome-wide suggesting a general role in splicing. Consistently, targeting of the H3K9 demethylase to a weak constitutive exon reduced co-transcriptional splicing. Together our data show H3K9 methylation within the gene body is a factor influencing recognition of both constitutive and alternative exons.
Keywords: Fibronectins; fibronektiny; lidé; Methylation; Humans; genetická transkripce; Lysine; lysin; Alternative Splicing; Histones; alternativní sestřih; Transcription Activator-Like Effectors; TAL efektory; exony; HeLa buňky; HeLa Cells; Chromatin; Transcription, Genetic; histony; Exons; metylace; chromatin